Implantes nanotopograficamente modificados pela ação do laser Yb-YAG - Sisiti, Karin Ellen [UNESP]; Guastaldi, Antonio Carlos [UNESP]; Tavares, Hewerson Santos [UNESP]; Antoniolli, Andreia M. Brochado; Queiroz, Thallita P. [UNESP]; Souza, Francisley Ávila [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP]; Piatelli, Adriano; Marcantonio Júnior, Elcio [UNESP]; Pontes, Elenir Rose Jardim Cury [UNESP]; Rossi, Rafael de (My University, 2011)
Titanium has proven its suitability as an implant material in surgery over many years. Excellent biocompatibility and corrosion resistance are outstanding features. Implant surfaces always causes concern and interest in scientific communities, due to its close relationship with the time required for osseointegration. Surface modification can be performed by several methods, being laser irradiation one of them. Titanium implants with two different surfaces were inserted in rabbits: Group I (G-I: machined surface, control group), and group II (G-II: laser irradiated, test group) being processed 30 and 60 days after surgery for histological analysis. Surface characterization was performed with SEM-EDS, contact angle measurement, and mean roughness (Ra) parameters. Surface analysis in the GII group showed a nanomorphology affected by melt and quick solidification zones following laser irradiation (SEM), as well as total wettability and Ra mean values significantly higher than in the G-I group. The laser treatment resulted in a homogenized, porous surface, with increased surface area and volume. Histological analysis of bone-implant contact linear extension (BIC) showed better results in G-II at 30 days (39.26 ± 18.23 and 68.41 ± 13.68 for G-I and G-II groups, respectively). Titanium implants modified by laser irradiation showed important features that may accelerate early osseointegration.

O titânio como biomaterial apresenta excelente biocompatibilidade e resistência à corrosão. Vários estudos foram realizados nas últimas décadas sobre modificação da superfície dos implantes de titânio, a fim de otimizar o processo da osseointegração; o uso do laser é um dentre eles. Objetivo: o propósito deste estudo foi avaliar implantes de titânio modificados por feixe de laser de alta intensidade, comparando-os com os implantes usinados, por meio de análise topográfica e histométrica. Métodos: implantes de titânio com duas superfícies diferentes foram inseridas em tíbia de 30 coelhos (um de cada lado, escolhidos de forma aleatória). Grupo I (GI) superfície usinada (grupo controle) e Grupo II (GII) superfície irradiada com laser Yb-YAG (Pulsed Ytterbium Fiber Laser). A caracterização das superfícies foi realizada por meio de MEV-EDS, ângulo de contato e rugosidade média (Ra). Após 30 e 60 dias pós-operatórios, os animais foram submetidos à eutanásia e os implantes foram removidos para análise histológica da interface osso/implante. Resultados: a microfotografia do GII mostrou superfície rugosa e homogênea, com molhabilidade total e rugosidade maior do que o GI. A análise histológica da extensão linear de contato entre o tecido ósseo e a superfície do implante (Elcoi) revelou melhores resultados no GII aos 30 dias (39,26 ± 18,23 e 68,41 ± 13,68, para GI e GII, respectivamente). Conclusão: os implantes de titânio modificados por laser mostraram importantes características superficiais que favoreceram uma precoce osseointegração.
Nanofeatured dental implants by Yb-YAG laser modification
Keywords: Lasers; Titânio; Implantes dentários; Osseointegração; Coelhos; Lasers; Titanium; Dental implants; Osseointegration; Rabbits